Plastinated Knee Specimens: A Novel Educational Tool - Neha; Sanjeev Lalwani; Renu Dhingra (Journal of Clinical and Diagnostic Research, 2013)
Introduction: During the routine dissection of knee joints in an anatomy dissection hall, it was observed that the specimens had deteriorated overtime, due to their repeated handling and the use of high concentrations of formalin for their fixation. In order to stop their further deterioration, we decided to plastinate these specimens. Thus, the present study was undertaken to prepare plastinated knee specimens from old embalmed cadavers and to compare them with freshly fixed, plastinated specimens. Objectives: 1. To plastinate old embalmed and fresh formalin fixed knee regions. 2. To demonstrate the extra and the intracapsular structures around both the plastinated knee regions. 3. To compare their morphological features in terms of their colours, dilatation and flexibility. Methods: A total of 15 knee joint specimens from among fresh formalin (5-8%) fixed (group I) and old embalmed bodies (group II) were collected, washed and plastinated by using the standard S-10 silicon technique and they were compared for their colours, dilatation and flexibility. Results: All the plastinated specimens showed an accurate reproduction of the tissue details that were comparable to those of the natural unfixed specimens. A comparison among the two groups showed a significant difference in terms of the colour, dilatation and the flexibility of the specimens. The plastinated knee joint specimens from group I were of good quality, with negligible shrinkage, more flexibility and well preserved morphologies. Conclusion: Plastinated knee specimens can serve as an excellent educational tool for the undergraduate and postgraduate students of anatomy, radiology and orthopaedics, as they are dry, odourless and nontoxic, with a good structural preservation and a higher instructional value. The fresh knee regions, when they were plastinated, were aesthetically superior in terms of their colours, dilatation and flexibility, thus making them ideal for teaching and hands-on experiences.